Effect of Cognitive-Behavioral Intervention on Burden of Family Caregivers of Patients with Alzheimer\\\'s Disease - Ladan Bagherbeik Tabrizi; Elham Navab; Pouya Farokhnezhad Afshar; Ahmad Ali Asadi Noghabi; Hamid Haghani (Tehran University of Medical Sciences, 2015)
Background & Aim: Family caregivers play major role in caring for the patients with dementia. Meanwhile, they are at risks of various diseases. Caring for a person with Alzheimer's disease carries a significant physical, socioeconomic and psychological burden. This study described the impact of cognitive-behavioral management on burden and problems borne by family caregivers of patients with Alzheimer's disease .   Methods & Materials: This non-randomized controlled clinical trial was conducted on 70 family caregivers of patients with Alzheimer's disease. The participants were subjected to experimental and control groups. The Zarit Burden Interview was used to assess the burden experienced by family caregivers of the patients. Data were then analyzed using inferential and descriptive statistical parameters (mean and SD) and paired sample t-test on the difference between the scores of pre-test and post-test .   Results: The mean level of caregivers' burden as measured by ZBI was 44.56± 6.77 and 42.57±5.98, in experimental and control groups before intervention respectively. Caregivers' burden score was 39.54±5.88 and 44.86±5.87, in experimental and control groups after intervention respectively. Results showed a significant decrease in the training group's score (P<0.001) .   Conclusion: Given the obtained results indicating the effectiveness of cognitive- behavioral management in reduction of caregivers' burden, the present study can be helpful in achieving an effective solution to decrease stress among family caregivers of patients who suffer from Alzheimer's disease .